Visual Disability Among Juvenile Open-angle Glaucoma Patients. Issue 4 (April 2018) - Gupta, Viney; Ganesan, Vaitheeswaran L.; Kumar, Sandip; Chaurasia, Abadh K.; Malhotra, Sumit; Gupta, Shikha
Abstract : Aim: Juvenile onset primary open-angle glaucoma (JOAG) unlike adult onset primary open-angle glaucoma presents with high intraocular pressure and diffuse visual field loss, which if left untreated leads to severe visual disability. The study aimed to evaluate the extent of visual disability among JOAG patients presenting to a tertiary eye care facility. Methods: Visual acuity and perimetry records of unrelated JOAG patients presenting to our Glaucoma facility were analyzed. Low vision and blindness was categorized by the WHO criteria and percentage impairment was calculated as per the guidelines provided by the American Medical Association (AMA). Results: Fifty-two (15%) of the 348 JOAG patients were bilaterally blind at presentation and 32 (9%) had low vision according to WHO criteria. Ninety JOAG patients (26%) had a visual impairment of 75% or more. Conclusions: Visual disability at presentation among JOAG patients is high. This entails a huge economic burden, given their young age and associated social responsibilities.